Empathy as a Predictor of Religious Moderation Among Adolescents: Evidence from Indonesian Senior High School Students - Darmawansyah Darmawansyah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2026)
This study aims to determine the effect of empathy on religious moderation among students at State Senior High School 4 Palu. Religious moderation is crucial for adolescents in fostering attitudes of tolerance, inclusivity, and mutual respect. Furthermore, empathy is an internal psychological factor that warrants further investigation. This study employs a quantitative approach using a survey design. The population consists of 303 students, selected via random sampling with a margin of error of 0.05. The study utilizes the Perth Empathy Scale (PES) to assess empathy levels and religious moderation, focusing on national commitment, tolerance, anti-violence attitudes, and cultural/local accommodation. For data analysis, the researcher used linear regression with SPSS version 20. This study indicates that empathy contributes to religious moderation with a coefficient of 48.91%. This study suggests that fostering empathy in character education is a critical focus that should be prioritized. Additionally, several approaches and methods can be employed in character education, such as experiential learning and reflective learning with a focus on social interaction.